RELIGIOUS VALUES IN BALINESE HINDUISM DEATH RITUALS: AN ANTHROPOLOGICAL PERSPECTIVE - Abdullah Muslich Rizal Maulana; Syamsul Hadi Untung; Hanin Alfia Rosyidah (Lembaga Penelitian Universitas Pasundan, 2022)
This paper highlighted the religious values of Balinese Hinduism death rituals in the framework of Anthropology. This research utilized Typological and Content analysis methods to describe the classification of the different burial ceremonies of Balinese Hindus and then analyze its message properties within the literature. Perse, it is apparent that the religious values of Balinese Hinduism death rituals consisted of Pitra Yadnya as its very essence, following the guidance of the Almighty God, Sang Hyang Widhi Wasa. This research concluded that following an Anthropological approach, the Myth of Balinese Hinduism plays a decisive role in constructing the community’s belief system, which is associated with the emergence of diverse forms of rituals. As implementing the rituals focuses on adhering to the Sacred in its relation to the surrounding profane world, it is also clear that Balinese Hinduism death rituals occupy a holistic and cultural relativism position, which is vital in the Anthropological approach.